Justification of directions for improving authentication protocols in information and communication systems - Havrylova, Alla; Khokhlachova, Yuliia; Tkachov, Andrii; Voropay, Natalya; Khvostenko, Vladyslav (Національний авіаційний університет, 2023)
The analysis of information about the conducted cyber-threats makes it possible to identify modern information security problems when transmitted through unprotected communication channels. When conducting such an analysis, various components of the methods of implementing cyber threats are considered, but in this paper, it is proposed to pay attention to the motivational component of the emergence of threats and the existing effective tools for countering them. Such a comprehensive approach will make it possible to predict various modes of cyberattacks that cybercriminals can use against certain systems and to prepare the necessary digital security systems for the implementation of future threats. The influence of the exponential growth of the capacities of computing devices on the growth of the possibilities of implementing attacks by cybercriminals on cryptographic algorithms was also revealed. In this regard, the work considered the possibilities of increasing the level of resistance to such interventions, which are ensured by the NIST requirements for stability and security in the conditions of the post-quantum period. To determine the level of security of data transmission over an insecure network with privacy, integrity and authentication, a comparative analysis of the capabilities of information transmission protocols was conducted. The results of the analysis are presented in the form of a scheme of security and stability of protocols and algorithms that made it to the finals of the NIST competition. To ensure the integrity and authenticity of users when establishing communication sessions with websites, it is recommended to use TLS protocols. A scheme of the process of authenticated encryption and verification ofthe authenticity of an encrypted message transmitted using a TLS connection has been developed. The process diagram of authentication encryption and decryption of information when establishing a communication session in TLS protocols has been developed. A comparative analysis of different versions of TLS protocols was carried out.

Аналіз інформації про проведені кіберзагрози дозволяє виявити сучасні проблеми безпеки інформації при передачі незахищеними каналами зв язку. При проведенні такого аналізу враховують різні складові методів реалізації кіберзагроз, але в даній роботі за-пропоновано звернути увагу на мотиваційну складову виникнення загроз й існуючи дієві інструменти протидії їм. Такий комплексній підхід дозволить спрогнозувати різні режими кібератак, які кіберзлочинці можуть застосувати проти певних систем та підготувати необхідні цифрові системи безпеки при реалізації майбутніх загроз. Також було виявлено вплив експоненційного зростання потужностей обчислювальних пристроїв на зростання можливостей реалізації атак кіберзлочинцями на криптографічні алгоритми. У зв язку з цим в роботі були розглянуті можливості підвищення рівня протидії таким втручанням, які забезпечуються за допомогою вимог NIST до стійкості та безпековості в умовах постквантового періоду. Для визначення рівня безпековості передачі даних за не-безпечною мережею із забезпеченням приватності, цілісності та автентифікації, було проведено порівняльний аналіз можливостей протоколів передачі інформації. Результати аналізу представлені у вигляді схеми безпеки та стійкості протоколів та алгоритмів, які вийшли у фінал конкурсу NIST. Для забезпечення цілісності та справжності користувачів під час встановлення сеансів зв'язку з веб-сайтами рекомендовано використовувати TLS-протоколи. Розроблено схему процесу автентифікованого шифрування та перевірки справжності зашифрованого повідомлення, що пере-дається за допомогою TLS-з'єднання. Розроблено процесну схему автентифікаційного шифрування та розшифрування інформації при встановленні сеансу зв'язку в протоколах TLS. Проведено порівняльний аналіз різних версій протоколів TLS.
Обгрунтування напрямків вдосконалення протоколів автентифікації в інформаційно-комунікаційних системах
Keywords: authentication; TLS protocols; cyber threats; NIST; methods of implementing cyber threats; аутентифікація; TLS-протоколи; кіберзагрози; NIST; методи реалізації кіберзагроз